2023
DOI: 10.3390/diagnostics13081488
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Applications of Radiomics in Diagnosis, Staging, and Recurrence of Intrahepatic Cholangiocarcinoma

Abstract: Background: This paper offers an assessment of radiomics tools in the evaluation of intrahepatic cholangiocarcinoma. Methods: The PubMed database was searched for papers published in the English language no earlier than October 2022. Results: We found 236 studies, and 37 satisfied our research criteria. Several studies addressed multidisciplinary topics, especially diagnosis, prognosis, response to therapy, and prediction of staging (TNM) or pathomorphological patterns. In this review, we have covered diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 201 publications
0
2
0
Order By: Relevance
“…Multiple algorithms have been developed to characterize focal liver lesions as benign or malignant on US and CT, showing an AUC comparable to radiologist performance [ 44 , 45 , 46 ]. Other research focused on the automated differentiation of hepatocellular carcinoma from other malignant tumors, such as intrahepatic cholangiocarcinoma [ 47 , 48 ]. Yin et al developed a deep learning convoluted neural network (CNN) capable of distinguishing gallbladder cancer from benign gallbladder diseases on CT (AUC, 0.81; 95% CI 0.71–0.92) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple algorithms have been developed to characterize focal liver lesions as benign or malignant on US and CT, showing an AUC comparable to radiologist performance [ 44 , 45 , 46 ]. Other research focused on the automated differentiation of hepatocellular carcinoma from other malignant tumors, such as intrahepatic cholangiocarcinoma [ 47 , 48 ]. Yin et al developed a deep learning convoluted neural network (CNN) capable of distinguishing gallbladder cancer from benign gallbladder diseases on CT (AUC, 0.81; 95% CI 0.71–0.92) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In gastrointestinal imaging, it aids in the identification of biomarkers associated with disease progression and treatment response. Some softwares have a promised impact on evaluation of prostate cancer multiparametric MRI values, which need a preliminary long, spending time, images elaboration before Radiologist report with p-rads criteria [32][33][34][35][36][37][38][39][40][41].…”
Section: Organs Software Applicationsmentioning
confidence: 99%
“…Several studies have reported that AI tools can also predict outcomes and recurrence risk based on various clinical and genetic factors [24,38,53,108]. In this clinical scenario, AI should guide the physician during short-and long-term follow-up and surveillance of patients affected by CRC and LM.…”
Section: Current Status and Future Perspectivesmentioning
confidence: 99%